Danger zone assessment in small-sided recreational football: providing data for consideration in relation to COVID-19 transmission - Zoran Milanović; Magni Mohr; Peter Krustrup; Morten B Randers; Nikolas Sten Knudsen; Manuel Mounir Demetry Thomasen; Jeppe Panduro; Malte Nejst Larsen; Thomas Bull Andersen (BMJ Open Sport & Exercise Medicine)
Objectives This study investigated time spent with close contact (danger zone (DZ) within 1.5 m), number of contacts and time per contact, and compared game formats in recreational small-sided football games for young and adult male football players.Methods Movement analyses were performed on 10 Hz Global Positioning System (GPS) data collected during various small-sided football games prior to the COVID-19 outbreak.Results Time spent in the DZ was 4.3–7.9 s/h per per cent infected players, corresponding to 34.3–114.8 s/h if one player was infected. Number of contacts with one infected player was 23.5–87.7 per hour, with an average contact time of 1.1–1.4 s, and a total number of contacts of 311–691 per hour with all players. 53%–65% of all contacts were shorter than 1 s and 77%–85% shorter than 2 s. Trivial to small effects were found for number of participants and area per player, whereas standard of play and playing with/without boards had no effect.Conclusion This study demonstrated that during small-sided football limited time is spent within DZ and that player contacts are brief. Recreational football may therefore more appropriately be deemed as sporting activity with brief, sporadic contact.